Student's underground movement in Iloilo (1960-1992). - Singson, Ma. Clarizza Z (2002.)
The ever deepening crisis of the semi-feudal and semi-colonial set-up of the country paved the way to the resurgence of the revolutionary movement in the 1960's. The declaration of Martial Law on September 11, 1972, had declared student councils, publications and other student formations illegal. This had left no option to the progressive movement but to go underground. Thus, the underground movement in Iloilo was established., This research has four objectives: first is to trace the origin and development of the student's underground movement in Iloilo. Second: to sum up the periodic experiences of student's underground movement in Iloilo. Third, to find out the nature of its participation in the national democratic revolution. And lastly, to assess its contributions to the national democratic movement. This is a descriptive and testimonial study, hence, a personal interview was conducted and written questions were given to some of the informants. Informants were those who were members of the student's underground movement in Iloilo since 1960 up to the 1992. In tracing the origin and development of the student's underground movement in Iloilo proved that indeed it had existed before the Martial Law up to 1992. The gathered information shows that the student's underground movement had experienced a "flow and ebb" movement in terms of their consolidated strength and sphere of influence. Also, that it had participated in the national democratic revolution. Student's Underground Movement in Iloilo was the core of the revolutionary movement of the youth and students. It had contributed to and became an integral part of the National Democratic Movement.
Research Paper (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Student's Underground Movement